A smartphone application of diabetes coaching intervention to prevent the onset of complications and to improve diabetes self-management: A randomized control trial - Pamungkas R.A. (2023)
Background and aim: Diabetes mellitus (DM) has been a worldwide public health problem during the last two decades. To examine the effect of a smartphone application of diabetes coaching intervention on improving self-management behaviors and preventing onset diabetes complications. Methods: A randomized control trial, two groups, pre-test, and post-test design with a non-equivalent control group was conducted. The intervention group received a 12-week smartphone application of diabetes coaching intervention to improve diabetes self-management behaviors and to prevent onset diabetes complications. While the control group received the usual care from the community health centers. The smartphone application consisted of narrative App-based coaching, a printed user guide, mindfulness-based coaching; skill-based coaching, and a small App-interaction. Results: After implementation, the self-management behaviors among the experimental group were improved than the control group in terms of dietary control, physical exercise, blood glucose monitoring, medication adherence, and screening of complications. The clinical outcomes were also significantly improved among the experimental group and to the control group. Conclusions: A smartphone application-based diabetes coaching intervention was feasible to apply as a nationwide program to promote diabetes self-management (DSM) during the covid-19 pandemic